The Adam Smith review.
1 online resource (xxvi, 356 pages).
Keywords: Adam Smith's contribution to economics is well recognized, yet scholars have recently been exploring anew the multidisciplinary nature of his works. The Adam Smith Review is a rigorously refereed annual review that provides a unique forum for interdisciplinary debate on all aspects of Adam Smith's works, his place in history, and the significance of his writings to the modern world. It is aimed at facilitating debate among scholars working across the humanities and social sciences, thus emulating the reach of the Enlightenment world which Smith helped to shape.